Attachment and detachment of particles to and from fluid interfaces. (April 2022) - Vialetto, Jacopo; Zanini, Michele; Isa, Lucio
Abstract: In this topical review, we commemorate some of the outstanding contributions of Prof. Peter Kralchevsky in the field of colloid and interface science. In particular, we focus on his achievements on phenomena involving the attachment and detachment of colloidal particles to and from fluid interfaces, giving a personal perspective on how his work has inspired our own research and the activities of a thriving scientific community. We specifically concentrate our presentation on the issues of emulsion stability via particle adsorption and desorption, particle organization via capillary immersion forces and on the relevance of electrostatic barriers to spontaneous particle adsorption. This review takes the reader through numerous developments, from the early '90s to the present day, and reflects on the importance of the legacy of the work of Prof. Kralchevsky for the years to come.